2022
DOI: 10.1101/2022.01.30.22270124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of retracted randomised controlled trials on systematic reviews and clinical practice guidelines: a meta-epidemiological study

Abstract: Objectives To investigate whether and when the correction is done in Systematic Reviews (SRs) and Clinical Practice Guidelines (CPGs) when their included Randomised Controlled Trials (RCTs) have been retracted. Design A meta-epidemiological study. Data sources The Retraction Watch Database. Eligibility criteria for selecting studies SRs and CPGs citing the retracted RCTs on Web of Science. Review methods We investigated how often the retracted RCTs were cited in SRs and CPGs. We also investigated whether and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The impact of retracted papers on scientific knowledge and clinical practice can continue well after they are retracted. A preprint review has shown that systematic reviews and meta-analyses which include research which is later retracted are rarely, if ever, updated once the issues with the included research come to light, while nearly half of the reviews citing retracted papers were published after those papers were retracted (6). Key recommendations for proper retraction processes remain largely unimplemented across the scientific literature (7).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of retracted papers on scientific knowledge and clinical practice can continue well after they are retracted. A preprint review has shown that systematic reviews and meta-analyses which include research which is later retracted are rarely, if ever, updated once the issues with the included research come to light, while nearly half of the reviews citing retracted papers were published after those papers were retracted (6). Key recommendations for proper retraction processes remain largely unimplemented across the scientific literature (7).…”
Section: Introductionmentioning
confidence: 99%
“…Retracted studies have the most obvious flaws. Retraction is defined as the removal of a published paper from a journal to warn readers of the significant problems identified in the article as a means of maintaining the integrity of scientific literature [ 2 ]. Including retracted studies in a systematic review may impact the outcomes and level of evidence, and ultimately provide inaccurate medical guidelines [ 3 , 4 ].…”
mentioning
confidence: 99%